2018
DOI: 10.1002/joc.5521
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in climate extremes in China in a 1.5 °C warmer world

Abstract: In December 2015, the Paris Agreement was reached in an effort to limit global warming to below 1.5 °C. However, there is few scientific literature assessing changes in the climate with 1.5 °C of warming over China. We investigated changes in climate extremes in China that generally present high impacts on society. The results indicated that an additional warming of 0.5 °C would lead to significant increases in temperature and precipitation extremes across China. Both the temperatures on the hottest days and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 42 publications
8
45
1
Order By: Relevance
“…We test this hypothesis by examining events similar to the 2008 extreme cold winter in southern China ( Figure 5). This is consistent with that given by Chen and Sun (2018), who also indicated that the probability of individual extreme cold event would be rare under the 1.5°C and 2°C warming scenarios. This is consistent with that given by Chen and Sun (2018), who also indicated that the probability of individual extreme cold event would be rare under the 1.5°C and 2°C warming scenarios.…”
Section: Earth's Futuresupporting
confidence: 92%
See 2 more Smart Citations
“…We test this hypothesis by examining events similar to the 2008 extreme cold winter in southern China ( Figure 5). This is consistent with that given by Chen and Sun (2018), who also indicated that the probability of individual extreme cold event would be rare under the 1.5°C and 2°C warming scenarios. This is consistent with that given by Chen and Sun (2018), who also indicated that the probability of individual extreme cold event would be rare under the 1.5°C and 2°C warming scenarios.…”
Section: Earth's Futuresupporting
confidence: 92%
“…In the context of global warming, summers in China will become warmer and the probability of extreme summer heat will increase. However, our result shows a larger probability of such hot extreme events in a 1.5°C or 2°C warmer world than that in Chen and Sun (2018) using the RCP scenario simulations. This finding is consistent with analyses for Europe conducted by Stott et al (2004) and Christidis et al (2015).…”
Section: Earth's Futurecontrasting
confidence: 69%
See 1 more Smart Citation
“…In other regions elsewhere, such as East Asia, North America, Europe, and Australia, there have been extensive studies on climate change impacts at 1.5 and/or 2 °C of global warming (e.g., H. Chen & Sun, ; King & Karoly, ; King et al, ; Li, Zhou, et al, ; Li, Zou, & Zhou, ; Yohe, ). Limiting global warming to 1.5 °C instead of 2 °C may have benefits of avoiding 35–46% of the increases in extreme temperature events in terms of intensity, duration, and frequency across East Asia (Li, Zhou, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Australia; and Vautard et al (2014) for Europe; Osima et al (2018) and Nkemelang et al (2018) for Africa; Swain and Hayhoe (2015) and Karmalkar and Bradley (2017) for the United States; Xu et al (2017), Chen and Sun (2018), , , Shi et al (2018), and Zhao and Zhou (2019) for East Asia (EA).…”
Section: Introductionmentioning
confidence: 99%